Continuous intake of the Chaga mushroom (Inonotus obliquus) aqueous extract suppresses cancer progression and maintains body temperature in mice. Issue 5 (May 2016) - Arata, Satoru; Watanabe, Jun; Maeda, Masako; Yamamoto, Masato; Matsuhashi, Hideto; Mochizuki, Mamiko; Kagami, Nobuyuki; Honda, Kazuho; Inagaki, Masahiro
Abstract: Aims: Cancer is a leading cause of morbidity and mortality worldwide; therefore, effective measures for cancer prevention and treatment are in constant demand. The extracts of Inonotus obliquus (Chaga mushroom) demonstrate potent anti-tumor activities and have been used to treat cancer in several countries; however, the actual effect and underlying mechanisms are still unclear. In the present study, we aimed to investigate the effects of continuous intake of aqueous extract from I. obliquus on tumor suppression. Main methods: Anticancer activity of the I. obliquus extract was examined in mouse models of Lewis lung carcinoma growth and spontaneous metastasis after 3 weeks of continuous extract intake at the dose of 6 mg/kg/day, which corresponded to that ingested daily with Chaga infusion in Japan. Key findings: The extract of I. obliquus caused significant tumor suppressive effects in both models. Thus, in tumor-bearing mice, 60% tumor reduction was observed, while in metastatic mice, the number of nodules decreased by 25% compared to the control group. Moreover, I. obliquus extract-treated mice demonstrated the increase in tumor agglomeration and inhibition of vascularization. Interestingly, I. obliquus intake decreased body weight in middle-aged mice and increased body temperature in response to light-dark switching in mature adult mice. Furthermore, I. obliquus prevented temperature drop in mice after tumor implantation. Significance: Our findings suggest that the I. obliquus extract could be used as a natural remedy for cancer suppression by promoting energy metabolism.